1977
DOI: 10.1126/science.140460
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and Fibroblast Chalones: Some Chemical Properties

Abstract: Experiments with lymphocyte and fibroblast chalones indicate that they are complexed strongly with RNA in tissue extracts; have a molecular weight of less than 10,000 and more than 1,000 daltons, and probably about 5,000 daltons; are strongly cationically charged; and contain mannose and perhaps other carbohydrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The existence of a number of growth inhibitors has been postulated (1,2), and growth-inhibitory fractions have been obtained from various mammalian cells and tissues (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Nevertheless, there are doubts as to the significance of endogenous growth inhibitors because most of the inhibitor preparations have low specific activity, the inhibitors have been difficult to purify, and with some preparations the causes of growth inhibition have, at least in part, turned out to be trivial (15)(16)(17).…”
mentioning
confidence: 99%
“…The existence of a number of growth inhibitors has been postulated (1,2), and growth-inhibitory fractions have been obtained from various mammalian cells and tissues (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Nevertheless, there are doubts as to the significance of endogenous growth inhibitors because most of the inhibitor preparations have low specific activity, the inhibitors have been difficult to purify, and with some preparations the causes of growth inhibition have, at least in part, turned out to be trivial (15)(16)(17).…”
mentioning
confidence: 99%
“…An (1978) described which binds avidly to RNA (11). This sse differs from ours in being readily inactivated by proteases, and it is also active on phytohemagglutinin-stimulated human lymphocytes which are known to be thiol independent.…”
Section: Discussionmentioning
confidence: 65%
“…endog enous inhibitor of lymphocyte response in vitro (lectin and alloantigcn stimulation) and in vivo (skin allograft rejection). Further studies with the ultrafiltrate from calf thymus [6,7] showed that the inhibitory activity could be converted to low molecular weight by treatment of the ultrafiltrates with ribonu cléase or low pH. These results suggest that the inhibitor was bound to high molecular weight carrier molecules.…”
Section: Introductionmentioning
confidence: 76%